IKLIM DAN POTENSI TEGAKAN SENGON (Falcataria moluccana) DI HUTAN RAKYAT DESA JATI BALI KABUPATEN KONAWE SELATAN - Aminuddin Mane Kandari; Safril Kasim; La Ode Agus Salim Mando; La Ode Midi; Suhartin Triyani Palebangan (Jurnal Belantara, 2020)
This study aims to determine the climatic conditions that occur at Sengon cultivation sites and determine the standing potential number of trees, base area, and volume of sengon stands in community plantation forests that follow the people's seed garden program. Data collection is carried out in August to November 2018.  The location of this village is at the coordinates of 04° 5'12 '' - 04°3'15'' LS and 122° 24'00'' - 122° 23'00'' BT and at altitude of 108 m above sea level. The population in this study is the sengon stand with an area of 5.8 ha. The sample area is determined with an intensity of 6.2% and the area of 1 plot is 0.04 ha, so the number of plots is 9 units. The results showed that 1) climatic conditions in the study location are classified as type B climate or wet (Schmidth-Ferguson method) including the category of tropical rain forests with an average number of wet months (BB) 9.2 and dry months (BK) 1.5 with a Q value of 0.16. Average annual rainfall is 2 662.6 mm, the monthly average rainfall of the highest in May was 347.4 mm with an average number of  rainy days by 22.5 days and the lowest in September was 83.0 mm with an average rainy day of 11 days, while the longest rainy day occurred in April during 22.6 days with rainfall reaching 262.1 mm and the fastest occurred in October for 10.3 days with rainfall reaching 101.7 mm. The average annual temperature is around 230C with an  320C, with the lowest monthly average of 25.3oC (August) - 28.1oC (December). This fact indicates that the climatic conditions in Jati Bali Village South Konawe District are suitable for the development of sengon plants. 2) the potential of sengon stands in the village of Jati Bali South Konawe Regency, namely the number of trees 866 btgha-1, base area of 9.76 m2ha-1, volume of stands of 94.15 m3ha-1.